2014
DOI: 10.1039/c4ob01246a
|View full text |Cite
|
Sign up to set email alerts
|

Novel ruthenium-catalyst for hydroesterification of olefins with formates

Abstract: An alternative ruthenium-based catalyst for the hydroesterification of olefins with formates is reported. The good activity of our system is ensured by the use of a bidentate P,N-ligand and ruthenium dodecacarbonyl. A range of formates can be used for selective alkoxycarbonylation of aromatic olefins. In addition, the synthesis of selected aliphatic esters is realized. The proposed active ruthenium complex has been isolated and characterized.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…As shown in Table , we began our investigation by screening conditions for the decarboxylative–decarbonylative reaction of 2-( tert -butyl)-2-oxoacetic acid ( 1a ). To our delight, the only desired decarboxylation–decarbonylation product 3a , (in a good yield of 71%) was observed at 25 °C by irradiation with blue LEDs with Ir­[dF­(CF 3 )­ppy] 2 ­(dtbbpy)­PF 6 as the photocatalyst, NaOAc as the base, and benzyl acrylate ( 2a ) as the alkyl radical acceptor (entry 1). When Ir­(ppy) 2 ­(dtbbpy)­PF 6 was used instead of Ir­[dF­(CF 3 )­ppy] 2 ­(dtbbpy)­PF 6 , the yield of the product 3a was drastically decreased to 24% (entry 2).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table , we began our investigation by screening conditions for the decarboxylative–decarbonylative reaction of 2-( tert -butyl)-2-oxoacetic acid ( 1a ). To our delight, the only desired decarboxylation–decarbonylation product 3a , (in a good yield of 71%) was observed at 25 °C by irradiation with blue LEDs with Ir­[dF­(CF 3 )­ppy] 2 ­(dtbbpy)­PF 6 as the photocatalyst, NaOAc as the base, and benzyl acrylate ( 2a ) as the alkyl radical acceptor (entry 1). When Ir­(ppy) 2 ­(dtbbpy)­PF 6 was used instead of Ir­[dF­(CF 3 )­ppy] 2 ­(dtbbpy)­PF 6 , the yield of the product 3a was drastically decreased to 24% (entry 2).…”
Section: Resultsmentioning
confidence: 99%
“…Bidentate coordination of such heteroaryl phosphines (imidazole or pyridine) with as econd bonding interaction between nitrogen and ruthenium has been reported. [69][70][71][72] Nevertheless, we found that it does not substitute one carbonyl ligand. Relative band positions in the vibrational spectra obtained from DFT calculations on [Ru(CO) 4 (PPh 3 )] point to atetracarbonyl complex ( Figure 8a,b).…”
Section: Molecularstructures Of Mononuclear Complexesmentioning
confidence: 86%
“…We found that am onophosphine L4,w hich is similar to L1 but has an additional methylene group between the phosphorus atom and the imidazolyl moiety,g ives rise to ac omplex of the type [Ru(CO) 3 L]i nw hich the imine nitrogen atom substitutes one carbonyl ligand so that L coordinatesi nabidentate fashion (see Figure 8c). [71] The molecular structure was verified by X-ray crystal structure analysis. In concert with this structure, an obvious shift in frequencyf or the imine nitrogen atom was found by 1 H, 15 N HMBC NMR spectroscopy (d( 15 N, free L4) = À117ppm versus [20] inferiorr esultsw ere noted when the cyclohexyl groups of ligandsw ere substituted by tert-butyl or adamantyl groups.T he yields of aldehydesc ollapsed almostc ompletely.…”
Section: Molecularstructures Of Mononuclear Complexesmentioning
confidence: 99%
“…The combined organic phase was washed with brine, dried over Na 2 SO 4 , filtered, and concentrated under an aspiratory vacuum to give nonanoic acid ( 32 ) (16 mg) as an oil (71% purity, confirmed by 1 H NMR). Further purification by silica gel column chromatography (hexane:toluene = 1:1) after benzylation using above-mentioned procedure for 12 gave pure benzyl nonanoate (1.5 mg) as a pale yellow oil 53 : IR (neat): ν = 2954, 2925, 2855, 1736, 1456, 1156, 1108, 734, 696 cm −1 ; 1 H NMR (500 MHz, CDCl 3 ) δ 7.40–7.30 (m, 5 H), 5.11 (s, 2 H), 2.35 (t, J = 7.5 Hz, 2 H), 1.64 (quint, J = 7.5 Hz, 2 H), 1.35–1.20 (m, 10 H), 0.87 ppm (t, J = 7.5 Hz, 3 H); 13 C NMR (125 MHz, CDCl 3 ): δ = 173.7, 136.2, 128.5, 128.2 (3 C), 66.1, 34.4, 31.8, 29.2, 29.14, 29.12, 25.0, 22.6, 14.1 ppm; MS: m/z (%): 248 (2) ( M + ), 108 (33), 91 (100), 77 (10), 65 (15) (Fig. 6 ).…”
Section: Methodsmentioning
confidence: 99%